The factors affecting the acceptance of mobile banking in Kota Bharu, Kelantan / Nor Farhana Ilias - Ilias, Nor Farhana (2013)
Over the past several years, the wireless and mobile market has become one of the fastest growing markets in the world and it is still growing at a rapid rate. Because of this situation, all banks in Malaysia are expected to participate in mobile banking service by the middle year of 2013), says e-payment service provider, Malaysian Electronic Clearing Corp Sdn Bhd (MyClear). With mobile banking technology, bank may offer wide range of services to their customers such as doing funds transfer, check account balances, do a transaction, pay bills and others. Many Malaysian banks adopted mobile banking in the 2000s and it is a feature that continues to spread worldwide. Mobile banking operates similarly to other types of banking except for a few key differences: you only need to enter a Personal Identification Number (PIN) to access your secure accounts and you can receive banking information instantly anywhere in the world with cell phone reception. The aim of this study is to determine the factors affecting the acceptance of mobile banking in Kota Bharu, Kelantan. The questioners will be distributed to the banking customers